FAZLUR RAHMAN : PEMIKIRAN TENTANG HADIS\ DAN SUNNAH - Marita Lailia Rahman (Tribakti: Jurnal Pemikiran Keislaman, 2015)
This article explain about the thought of neo modern intellectual Fazlur Rahman about Hadis and Sunnah. Fazlur Rahman has thought about intellectual works related with study of Hadis\ begins by Sunnah’s concept of Islamic history to the Hadis Formalization.  Based on his thought, Sunnah’s concept is real and occurred since the beginning Islam and will be all of time. Rahman also clarify that Hadis\ have verbal characterictic whereas Sunnah have non verbal characteristic. Rahman use sosio-historis method to study the compatibility of text contents (Matan of Hadis\) with Qur’an. As his effort, Rahman want to return Hadis to the position as in the first history and create Islam as viable religion.